The Effect of Total Meniscectomy versus Caudal Pole Hemimeniscectomy on the Stifle Joint of the Sheep - Simpson, D. S.; Bellenger, C. R.; Ghosh, P.; Numata, Y.; Little, C. (Veterinary and Comparative Orthopaedics and Traumatology, 1999)
Total medial meniscectomy and caudal pole hemimeniscectomy were performed on the stifle joints of twelve sheep. The two forms of meniscectomy produced a comparable degree of postoperative lameness that resolved within two weeks of the operations. After six months the sheep were euthanatised and the stifle joints examined. Fibrous tissue that replaced the excised meniscus in the total meniscectomy group did not cover as much of the medial tibial condyle as the residual cranial pole and caudal fibrous tissue observed following hemimeniscectomy. The articular cartilage from different regions within the joints was examined for gross and histological evidence of degeneration. Analyses of the articular cartilage for water content, glycosaminoglycan composition and DNA content were performed. The proteoglycan synthesis and release from explanted articular cartilage samples in tissue culture were also measured. There were significant pathological changes in the medial compartment of all meniscectomised joints. The degree of articular cartilage degeneration that was observed following total meniscectomy and caudal pole meniscectomy was similar. Caudal pole hemimeniscectomy, involving transection of the meniscus, causes the same degree of degeneration of the stifle joint that occurs following total meniscectomy.The effect of total medial meniscectomy versus caudal pole hemimeniscectomy on the stifle joint of sheep was studied experimentally. Six months after the operations gross pathology, histopathology, cartilage biochemical analysis and the rate of proteoglycan synthesis in tissue culture were used to compare the articular cartilage harvested from the meniscectomised joints. Degeneration of the articular cartilage from the medial compartment of the joints was present in both of the groups. Caudal pole hemimeniscectomy induces a comparable degree of articular cartilage degeneration to total medial meniscectomy in the sheep stifle joint.
Keywords: Meniscectomy; hemimeniscectomy; stifle; articular cartilage; sheep; osteoarthritis